The Combination of Real-Time PCR and HPLC for the Identification of Non-Tuberculous Mycobacteria - Park, Jae Sun (The Korean Society for Laboratory Medicine, 2013)
We used HPLC and AdvanSure real-time PCR (LG Life Sciences, Korea) to retrospectively analyze non-tuberculous mycobacteria (NTM) in 133 clinical specimens. The specimens were culture-positive for NTM and the HPLC method identified 130 strains of mycobacteria from the cultures (97.7%) at the species level. Among the isolates, 48 Mycobacterium. kansasii (36.1%), 39 M. intracellulare (29.3%), 17 M. avium (12.8%), 16 M. abscessus (12.0%), 6 M. fortuitum (4.5%), 2 M. szulgai (1.5%), 2 M. gordonae (1.5%), and 3 unclassified NTM strains (2.3%) were identified. The real-time PCR assay identified 60 NTM-positive specimens (45.1%), 65 negative specimens (48.9%), and 8 M. tuberculosis (TB)-positive specimens (6.0%). The real-time PCR assay is advantageous because of its rapid identification of NTM. However, in our study, the real-time PCR assay showed relatively low sensitivity (45.1%) when using direct specimens including sputum and bronchoalveolar lavage (BAL) fluid. HPLC is useful as it discriminates NTM at the species level, although it is time-consuming and requires specific equipment and technical expertise. A combination of both methods will be helpful for the rapid and accurate identification of mycobacteria in clinical laboratories.